Meta-Analysis: A Comparison of Aspirin vs Doacs in Stroke Prevention for Atrial Fibrillation Patients with Low Chaâ‚‚Dsâ‚‚-Vasc Score - Elnaggar, Khaled; Imaz, Inshrah; Fatima, Asiya; Siddiqui, Tuba Manzoor; Roy, Jees; Kandy, Muhammad Shazin Vatta; alziyadah, Abdulrahman Ozair; Khalid, Saif; Raja, Usama Zahid (Cardiology and Cardiovascular Medicine, 2025)
Background: Atrial Fibrillation (AF) is the most prevalent cardiac arrythmia and a major risk factor for ischemic stroke. CHA2DS2-VASc score is used to stratify stroke risk in AF patients. Score of 0 for men and 1 for women are regarded as low risk. Whether anticoagulation is required in this population or not, have always been difficult to determine by clinicians. Historical use of aspirin led to its prescription, however, it has a limited ability to prevent stroke and risk of bleeding is high. Moreover, in higher risk groups, direct oral anticoagulants (DOACs) have proven to be more effective but its effectivity in low-risk patients is still under discussion. Objective: The main goal of this study is to systematically compare the safety and efficacy of DOACs and aspirin to prevent ischemic stroke in patients with atrial fibrillation who have low CHA2DS2-VASc scores. Methods: Systematic review of peer-reviewed studies was conducted, including observational cohort studies and randomized controlled trials, that were published between 2015 and 2025. Studies that directly compared the clinical outcomes of DOAC and aspirin treatment were eligible if they included adult patients with non-valvular AF and a CHA2DS2-VASc score of 0 (for men) or 1 (for women). All-cause mortality, major bleeding events and the incidence of ischemic stroke were the main outcomes evaluated. Random-effects models were used to pool the data, and the I2 statistic was used to measure heterogeneity. Results: With DOACs, the risk of ischemic stroke was approximately 37% lower than with aspirin (combined odds ratio [OR]: 0.63; 95% CI: 0.45–0.88; I2 = 29%). Although the DOAC group experienced major bleeding slightly more frequently (OR: 1.14), this difference was not statistically significant (95% CI: 0.85–1.52). Additionally, the overall death rates of the two groups under study were comparable. Subsequent analysis revealed that DOACs consistently offered a benefit to individuals with low CHA2DS2- VASc scores, regardless of age or risk level. Conclusion: In patients with atrial fibrillation and a low CHA2DS2-VASc score, DOACs offer better protection against ischemic stroke than aspirin, along with being safer when it comes to bleeding complications.